Exploring the Impact of Spaced Repetition Through Anki Usage on Preclinical Exam Performance - Victoria Winter; Emily Ames; Marley Jacobs; Carlos Georges; Edward Simanton (Journal of Medical Education and Curricular Development)
Background Medical knowledge is expanding rapidly at the same time as the preclinical phase of medical education is being shortened. This uniquely challenges medical students to learn efficiently and retain a large amount of information. Spaced repetition is a widely used learning technique and can be implemented through the use of a free downloadable program called Anki. Limited data exists on the use of spaced repetition through Anki and its impact on student performance in preclinical assessment, such as the Comprehensive Basic Science Subject Exam (CBSE). Methods This study evaluated Anki usage among 36 medical students at the Kirk Kerkorian School of Medicine at UNLV. Students consented to export their deidentified Anki data through the Stat Scraper add-on. Stat Scraper provided metrics on matured cards (those with an interval >21 days), total study hours, and number of unsuspended cards. Variables were correlated with CBSE exam scores and students were stratified into groups below and above the mean for each variable. Using this data, independent t-tests, Pearson Correlation coefficients and linear regressions were performed. Results Mean CBSE score was 65.2% (SD 11.6%). Linear regression demonstrated a significant positive correlation between the number of mature cards and exam scores. Significant positive correlations were also found between CBSE scores and total hours studied (P = 0.013), number of matured cards (P = 0.002), and unsuspended cards (P = 0.010). Students with above-average mature card counts scored 71.5% on the CBSE compared to 60.0% for those below average. Total study hours and unsuspended card counts similarly predicted higher scores. Conclusions Greater time spent using spaced repetition learning techniques through the Anki application and a higher number of matured and unsuspended cards were associated with increased performance on the CBSE exam. These findings support spaced repetition as an effective way for medical students to master and retain medical knowledge in the preclinical phase. Further research with larger sample sizes and more diverse populations is needed to validate these findings further.